Order Coleoptera Linnaeus, 1758. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Slipinski, S. A.; Leschen, R. A. B.; Lawrence, J. F. (Zootaxa, 2011)
-